Efisiensi Penyaluran Air Irigasi pada Saluran Primer Daerah Irigasi Tungkub - Debora Lydia Frida Tangkuman; I Wayan Tika; I Nyoman Sucipta; Ni Nyoman Sulastri; Mentari Kinasih (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2025)
Distribution efficiency is the balance value between the water discharge upstream and the water discharge downstream in minimizing the process of water loss. Generally, the water discharge distributed upstream will be greater than the water discharge downstream, due to water loss during distribution. However, there are cases where the amount of water discharge that reaches the downstream is actually greater than the amount of water distributed upstream, as happened in the primary channel of the Tungkub Irrigation Area. One of the causes of this difference in the amount of water discharge is due to the suppression during the distribution process. There are 10 to 15 suppression points available along the primary channel of Irrigation Tungkub Areas. This study aims to determine the efficiency of water distribution by calculating the amount of supplementary discharge and the efficiency of water distribution without calculating the amount of supplementary discharge. This research applies a quantitative analysis approach by collecting primary data, in the form of upstream water discharge data, downstream water discharge data, and supplementary discharge data along the primary channel during July to November 2023. From the calculation results, the result of the efficiency of water distribution with supplementation in the primary channel of DI Tungkub is 73,32% and the result of the efficiency of water distribution without calculating the amount of supplementation is 73,06%. Through this research, it can be concluded that supplementation affects the value of water distribution efficiency in the primary channel of DI Tungkub.